Penerapan Metode EOQ (Economic Order Quantity) dalam Meningkatkan Efisiensi Manajemen Inventori : Studi Kasus pada Toko Pakaian Lenkka di Majalengka - Hani Nurrohmah; Widya Retno Prasinta (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Lenkka Clothing Store is a business entity that operates in the online shop sector, especially in the sale of clothing products. With a main focus on the fashion industry. The data used in this study includes information on the purchase of trade goods or the supply of trade goods for Lenkka stores from two different convections, namely convections located in Majalengka and convections located in Bandung, other data includes sales volume, inventory costs, and other performance metrics from the period 2021 to 2023. This study aims to evaluate the effectiveness of the Economic Order Quantity (EOQ) Method in improving inventory management efficiency at Lenkka Clothing Store by measuring its impact on item availability, storage costs, and customer satisfaction. This research uses a quantitative approach with descriptive research. In this case, the research will describe the application of the EOQ method in improving inventory management efficiency at Lenkka Clothing Store in Majalengka.The data shows that the application of the EOQ Method has resulted in a reduction in Total Inventory Cost (TIC), optimization of inventory levels through safety stock and reorder point adjustments, and an increase in sales volume. In addition, the application of the EOQ Method is also proven to increase overall sales volume. The results of this study provide a clear picture of the benefits gained from applying the EOQ Method in the context of online business. This can be seen with the number of purchases for the 2021-2022 period amounting to 3,446.46 with a frequency of purchasing trade goods 55 times a year, savings of IDR 368,948,524, safety stock of 24,959 pcs and ROP of 68,598 pcs. The purchase amount for the 2022-2023 period is 3,179.86 with a frequency of purchasing trade goods 59 times a year, savings of Rp 343,213,678, safety stock 10,212 pcs and ROP 59,562 pcs. Thus, this research provides a comprehensive overview of the effectiveness of the application of the EOQ Method in the context of inventory management in online clothing stores.